Peran Teks Laporan Dalam Dokumentasi Dan Evaluasi Kegiatan Penelitian - Alya Rachma; Tifany Laura Balqis; Ameliya Harahap (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Research report is a document presenting the findings of a study, organized in accordance with a specific research method and mathematical approach, utilizing various languages. Fundamentally, the report should encompass three aspects: What needs to be reported, to whom it should be reported, and for whom it should be reported. These are typically displayed on the cover or title page. The text of the report plays a crucial role in documentation as it enables the collection, processing, and presentation of accurate and systematic information. In the context of research, the text of experimental and observational findings serves as documentation, allowing researchers to record data and outcomes obtained from the study. This research employs a qualitative method with an approach known as library studies. The findings of the research indicate challenges in organizing information systematically and clearly to be presented in a structured report. Authors may need to deal with complex data and analysis, requiring the ability to manage information effectively.